Supplementation with Milk-Derived Extracellular Vesicles Shapes the Gut Microbiota and Regulates the Transcriptomic Landscape in Experimental Colitis - Chunmei Du (Nutrients, 2022)
Harboring various proteins, lipids, and RNAs, the extracellular vesicles (EVs) in milk exert vital tissue-specific immune-protective functions in neonates via these bioactive cargos. This study aims to explore the anti-inflammatory effects of bovine milk-derived EVs on a dextran sulfate sodium (DSS)-induced colitis model and to determine the underlying molecular mechanisms. Sixty C57BL/6 mice were divided into the NC group (normal control), DSS group (DSS + PBS), DSS + LOW group (DSS + 1.5 × 108 p/g EVs), DSS + MID group (DSS + 1.5 × 109 p/g EVs), and DSS + HIG group (DSS + 1.0 × 1010 p/g EVs). Histopathological sections, the gut microbiota, and intestinal tissue RNA-Seq were used to comprehensively evaluate the beneficial functions in mitigating colitis. The morphology exhibited that the milk-derived EVs contributed to the integrity of the superficial epithelial structure in the intestine. Additionally, the concentrations of IL-6 and TNF-α in the colon tissues were significantly decreased in the EVs-treated mice. The abundances of the Dubosiella, Bifidobacterium, UCG-007, Lachnoclostridium, and Lachnospiraceae genera were increased in the gut after treatment with the milk-derived EVs. Additionally, the butyrate and acetate production were enriched in feces. In addition, 1659 genes were significantly down-regulated and 1981 genes were significantly up-regulated in the EVs-treated group. Meanwhile, 82 lncRNAs and 6 circRNAs were also differentially expressed. Overall, the milk-derived EVs could attenuate colitis through optimizing gut microbiota abundance and by manipulating intestinal gene expression, implying their application potential for colitis prevention.